2015
DOI: 10.1038/srep07704
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genetic characteristics of Saffold cardiovirus in China from 2009 to 2012

Abstract: The epidemiology and clinical features of the Saffold cardiovirus (SAFV) remain ambiguous. The present study was designed to systematically and intensively investigate the epidemiological features of SAFV in pediatric patients in China. Three cohorts of pediatric patients were recruited from 2009 to 2012. Cohort 1 comprised patients with acute respiratory tract infections. Cohort 2 comprised patients with diarrhea. Cohort 3 comprised hand, foot, and mouth disease (HFMD) patients. A total of 115 patients (1.6%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Phylogenetic analysis revealed that SAFV is closely related to Theiler’s murine encephalomyelitis virus (TMEV) [2, 3], a virus well studied for its neurovirulence [4]. Since then, SAFV have been isolated in children from multiple continents [1, 511] and have been shown to be highly prevalent in humans [7]. Recently, SAFV was found in the cerebrospinal fluid (CSF) of a previously healthy child that experienced sudden death [12], and in stool samples of children with non-polio acute flaccid paralysis [6], suggesting that the virus might be able to cause serious invasive infection of the central nervous system (CNS) of children [11].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phylogenetic analysis revealed that SAFV is closely related to Theiler’s murine encephalomyelitis virus (TMEV) [2, 3], a virus well studied for its neurovirulence [4]. Since then, SAFV have been isolated in children from multiple continents [1, 511] and have been shown to be highly prevalent in humans [7]. Recently, SAFV was found in the cerebrospinal fluid (CSF) of a previously healthy child that experienced sudden death [12], and in stool samples of children with non-polio acute flaccid paralysis [6], suggesting that the virus might be able to cause serious invasive infection of the central nervous system (CNS) of children [11].…”
Section: Resultsmentioning
confidence: 99%
“…Since then, SAFV have been isolated in children from multiple continents [1, 511] and have been shown to be highly prevalent in humans [7]. Recently, SAFV was found in the cerebrospinal fluid (CSF) of a previously healthy child that experienced sudden death [12], and in stool samples of children with non-polio acute flaccid paralysis [6], suggesting that the virus might be able to cause serious invasive infection of the central nervous system (CNS) of children [11]. TMEV, a virus similar to SAFV, is divided into two strains based on their neurovirulence after intracerebral inoculation [4]; the GDVII strain causes acute fatal poliomyelitis, killing all infected mice within 2 weeks, while DA strain causes milder encephalomyelitis, which then progresses to persistent infection and progressive demyelination reminiscent of multiple sclerosis [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, SAFV has been isolated from nasal and stool specimens of children with respiratory and gastrointestinal symptoms in many countries . To date, 11 genotypes of SAFV have been identified on the basis of phylogenetic analysis of the VP1 gene with SAFV‐2 and SAFV‐3 having high seroprevalence …”
Section: Introductionmentioning
confidence: 99%
“…Initial work with SAFV was hindered by poor growth in laboratory cell lines . Subsequently, it was discovered that selected cell lines were indeed able to support the growth of SAFV (dependent on strain) thus the exponential increase in research data in recent years . These cell lines include Vero, HeLa, NIH/3 T3, CHO‐K1, Hep‐2, and Neuro2A .…”
Section: Introductionmentioning
confidence: 99%